2022
DOI: 10.3389/fphar.2022.896523
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and Network Pharmacology Reveal the Protective Effect of Chaiqin Chengqi Decoction on Obesity-Related Alcohol-Induced Acute Pancreatitis via Oxidative Stress and PI3K/Akt Signaling Pathway

Abstract: Obesity-related acute pancreatitis (AP) is characterized by increasing prevalence worldwide and worse clinical outcomes compared to AP of other etiologies. Chaiqin chengqi decoction (CQCQD), a Chinese herbal formula, has long been used for the clinical management of AP but its therapeutic actions and the underlying mechanisms have not been fully elucidated. This study has investigated the pharmacological mechanisms of CQCQD in a novel mouse model of obesity-related alcohol-induced AP (OA-AP). The mouse OA-AP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Therefore, HDL may alleviate acute pancreatitis by activating the NRF2/HO-1-mediated ferroptosis pathway. Studies have shown that the severity of acute pancreatitis can be improved by inhibiting the PI3K/Akt pathway ( 35 ). Inhibiting scavenger receptor class B type I (SR-BI) is sufficient to cause apoptosis, elevated intracellular reactive oxygen species levels, and decreased PI3K/AKT signaling ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, HDL may alleviate acute pancreatitis by activating the NRF2/HO-1-mediated ferroptosis pathway. Studies have shown that the severity of acute pancreatitis can be improved by inhibiting the PI3K/Akt pathway ( 35 ). Inhibiting scavenger receptor class B type I (SR-BI) is sufficient to cause apoptosis, elevated intracellular reactive oxygen species levels, and decreased PI3K/AKT signaling ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 30 years, the Chinese herbal formula CQCQD has been widely used as an adjunctive therapy of conventional comprehensive treatment for AP in our hospital. A plethora of basic research studies from our group have revealed that CQCQD reduced pro-inflammatory indices and improved pancreatic and multiple organ injuries in experimental AP models [23,[49][50][51][52][53]. However, high-quality evidence from clinical studies to demonstrate its efficacy in AP patients is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a mouse model of obesity-related alcohol-induced acute pancreatitis chaiqin chengqi decoction (CQCQD) alleviated induced multi-organ dysfunction by decrease of AKT phosphorylation in pancreatic and adipose tissues. The network pharmacology analysis of all quality markers from the CQCQD revealed that six of them, among which is honokiol, possess high-affinity binding to AKT1 [138]. In a recent investigation, honokiol has stimulated adipocyte differentiation in murine adipocytes through SIRT3 activation.…”
Section: Compounds Of Other Chemical Classesmentioning
confidence: 99%